Offspring sex affects the susceptibility to maternal smoking-induced lung inflammation and the effect of maternal antioxidant supplementation in mice - Baoming Wang; Yik Lung Chan; Shengyu Zhou; Sonia Saad; Hui Chen; Brian G Oliver (BMC, 2020)
Abstract Background Cigarette smoke exposure (SE) during pregnancy is the largest modifiable risk factor for the development of lung disorders in offspring. We have previously shown that maternal L-Carnitine treatment can reduce the adverse impacts of maternal SE on renal and brain disorders in offspring. Here, we investigated the effect of maternal L-Carnitine supplementation on lung inflammatory pathways, autophagy, and mitophagy markers in the offspring in response to maternal SE. Methods Female BALB/c mice (8 weeks) were exposed to cigarette smoke for 6 weeks prior to mating, during gestation and lactation. Some of the SE dams were given L-Carnitine supplementation (1.5 mM in drinking water, SE + LC) during gestation and lactation. Lungs from the offspring were studied at birth and adulthood (13 weeks). Results At birth, in male offspring, there were increased levels of inflammatory markers (phosphorylated(p)-ERK1,2, p-P38 MAPK, p- NF-κB), and inflammasome marker (NLRP3), as well as mitophagy fission marker Drp-1 and autophagosome marker (LC3A/B-II) in the lung. Maternal L-Carnitine supplementation significantly reduced NLRP3 level. In contrast, maternal SE only increased IL1-β in female offspring, which was reversed by maternal L-Carnitine supplementation. At 13 weeks, there was an increase in LC3A/B-II and p- NF-κB in the male SE offspring with reduced p-JNK1,2, which were partially normalised by maternal L-Carnitine treatment. Female offspring were not affected by maternal SE at this age. Conclusion Maternal SE had adverse impacts on the male offspring's lung, which were partially alleviated by maternal L-Carnitine supplementation. Females seem to be less affected by the adverse effects of maternal SE.